2007
DOI: 10.1375/twin.10.5.757
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Genetic Study of Uric Acid and Liver Enzymes in Adolescent Twins

Abstract: Biochemical traits such as plasma alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma glutamyltransferase (GGT) and uric acid are associated with obesity, and with risk of cardiovascular disease, metabolic syndrome and diabetes. Each is subject to genetic influences, but little is known about changes in genetic and environmental influences on these traits over time. We investigated the contribution of genetic and environmental influences to variation in these biochemical traits in adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
4
10
0
Order By: Relevance
“…There were no strong associations across age groups; however, this is not inconsistent with previous reports, which have suggested that different genetic factors may act upon these phenotypes at different times [25,35]. The increased number of large test statistics relative to the expected distribution for the association with triacylglycerol suggests that common mitochondrial variants may influence this trait in early adolescence.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…There were no strong associations across age groups; however, this is not inconsistent with previous reports, which have suggested that different genetic factors may act upon these phenotypes at different times [25,35]. The increased number of large test statistics relative to the expected distribution for the association with triacylglycerol suggests that common mitochondrial variants may influence this trait in early adolescence.…”
Section: Discussionsupporting
confidence: 52%
“…The heritability estimates for each trait in our sample are high (Table 4), due to the heritability being estimated under an AE model, and there are strong phenotypic correlation across the three measurement time points [25,35,39]. Table 5 shows the most significant associations for each trait in the 12, 14 and 16 year age groups.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The heritability of liver function tests has previously been estimated in two twin studies [42,43]. Bathum et al investigated 290 pairs of elderly (age range 73-102 years) Danish same sex twins and found 35-61% heritability for S-ALT, S-GGT, serum bilirubin, serum albumin and serum lactate dehydrogenase [42].…”
Section: Discussionmentioning
confidence: 99%